STRUGGLES AND REWARDS OF PILOTING A THEATER GROUP IN LOW-INCOME HOUSING OF OLDER ADULTS. (16th November 2018) - Sutherland, L; Dunkle, R
Abstract: Older adults aging in place may experience social isolation. Participatory art programs can enhance social connectedness and confidence, thereby improving the health of older adults, but these programs are rarely created for low-income or marginalized older adults. A university social work department and community aging agency collaborated in establishing a professionally run theater group of older adults living in low-income housing in an urban area. The older adults attended a 12-week acting and improvisation skills class and performed a play. The original goal was for 30 residents to join the class but only 13 were recruited through the use of gift cards, presentations by community agency staff at the residences, and active engagement by the service coordinators. While the service coordinators attempted to recruit socially isolated residents, only 1 registered. The remaining members joined from general announcements. Attendance fluctuated over the duration of the class even with weekly reminder calls and letters, intercom announcements, and in-person conversations. Attendance ranged from 4–12 sessions. Pre and post data were gathered on measures of social connectedness including social isolation, community belonging, and social exclusion. Sense of community belonging increased for the participants, while the level of social exclusion remained the same. Results show that this type of activity is beneficial to residents who participate in the group but recruiting and sustaining participants in the class offers challenges. Ideas to address enrollment barriers as well as the role of the professionally trained teaching artist instructor in the maintenance of the program will be discussed.